JINGLE, a JCMT legacy survey of dust and gas for galaxy evolution studies: II. SCUBA-2 850 μm data reduction and dust flux density catalogues. Issue 3 (17th April 2019) - Smith, Matthew W L; Clark, Christopher J R; De Looze, Ilse; Lamperti, Isabella; Saintonge, Amélie; Wilson, Christine D; Accurso, Gioacchino; Brinks, Elias; Bureau, Martin; Chung, Eun Jung; Cigan, Phillip J; Clements, David L; et al.
ABSTRACT: We present the SCUBA-2 850$μ$ m component of JINGLE, the new JCMT large survey for dust and gas in nearby galaxies, which with 193 galaxies is the largest targeted survey of nearby galaxies at 850 $μ$ m. We provide details of our SCUBA-2 data reduction pipeline, optimized for slightly extended sources, and including a calibration model adjusted to match conventions used in other far-infrared (FIR) data. We measure total integrated fluxes for the entire JINGLE sample in 10 infrared/submillimetre bands, including all WISE, Herschel -PACS, Herschel -SPIRE, and SCUBA-2 850 $μ$ m maps, statistically accounting for the contamination by CO(J = 3–2) in the 850 $μ$ m band. Of our initial sample of 193 galaxies, 191 are detected at 250 $μ$ m with a ≥5σ significance. In the SCUBA-2 850 $μ$ m band we detect 126 galaxies with ≥3σ significance. The distribution of the JINGLE galaxies in FIR/sub-millimetre colour–colour plots reveals that the sample is not well fit by single modified-blackbody models that assume a single dust-emissivity index (β). Instead, our new 850 $μ$ m data suggest either that a large fraction of our objects require β < 1.5, or that a model allowing for an excess of sub-mm emission (e.g. a broken dust emissivity law, or a very cold dust component ≲10 K) is required. We provide relations to convert FIR colours to dust temperature and β for JINGLE-like galaxies. For JINGLE the FIR colours correlate more strongly with star-formation rate surface-density rather than the stellar surface-density, suggesting heating of dust is greater due to younger rather than older stellar-populations, consistent with the low proportion of early-type galaxies in the sample.